CHLOROPHYLL CONCENTRATION ANOMALY IN COASTAL MARINE AREA OF VIETNAM SOUTH CENTRE RELATED TO ENSO PHENOMENON - Tac, Vu Van; Hai, Doan Nhu (Vietnam Journal of Marine Science and Technology, 2018)
The studies on the impact of the ENSO phenomenon on climate and environment change have shown that the Bien Dong (Southeast Asia Sea) is strongly influenced by this phenomenon. This paper focuses on analyzing sea surface chlorophyll concentration data in the coastal marine area of Vietnam South Centre from MODIS satellite images of National Aeronautics and Space Administration (US NASA). The analysis results have shown that there is no obvious difference of the chlorophyll anomaly index between El Niño and neutral years. However, in La Niña years the chlorophyll anomaly index is greatly varied and generally inversely proportional to the ONI index, which means chlorophyll anomaly index rises while ONI index falls. The impact has made chlorophyll in summer and autumn of La Niña years higher by 0.22 - 0.38 mg/m3 in comparison with other years. In terms of trends, chlorophyll concentration in the Vietnam South Central Coast fluctuates according to the seasons and months. The average chlorophyll concentration usually reaches its maximum value in the Autumn (Sep. - Nov.), then decreases in the Winter (Dec. - Feb.) and usually reaches the minimum value in the Spring (Mar. - May), then rises gradually in the Summer (June - Aug.). The above results have contributed to improving understanding of the impact of the climatic vagaries on the coastal marine area of Vietnam South Centre, supported scientists and managers in proposing measures to prevent, avoid efficiently, limit and mitigate the damage caused by ENSO, and in having reasonable alternatives in the protection of biodiversity as well as environment in the coastal marine area of Vietnam South Centre. It could be considered as a “small piece” of the overall picture of the impacts of the ENSO phenomenon on global climate change.